2021
DOI: 10.1186/s40164-020-00197-9
|View full text |Cite
|
Sign up to set email alerts
|

AP-1 family transcription factors: a diverse family of proteins that regulate varied cellular activities in classical hodgkin lymphoma and ALK+ ALCL

Abstract: Classical Hodgkin lymphoma (cHL) and anaplastic lymphoma kinase-positive, anaplastic large cell lymphoma (ALK+ ALCL) are B and T cell lymphomas respectively, which express the tumour necrosis factor receptor superfamily member, CD30. Another feature shared by cHL and ALK+ ALCL is the aberrant expression of multiple members of the activator protein-1 (AP-1) family of transcription factors which includes proteins of the Jun, Fos, ATF, and Maf subfamilies. In this review, we highlight the varied roles these prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 147 publications
(228 reference statements)
0
49
0
Order By: Relevance
“…CXCLs facilitate angiogenesis and other pathways to promote tumor cells to obtain different proliferation and metastasis potentials 39 . Third, AP-1 family transcription factors regulate a variety of cellular activities in classical Hodgkin's lymphoma and anaplastic large cell lymphoma 40 . Whether CXCLs and their associated genes also promote tumor proliferation, inhibit apoptosis, and evade host immune responses through the AP-1 and NF-κB pathways remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…CXCLs facilitate angiogenesis and other pathways to promote tumor cells to obtain different proliferation and metastasis potentials 39 . Third, AP-1 family transcription factors regulate a variety of cellular activities in classical Hodgkin's lymphoma and anaplastic large cell lymphoma 40 . Whether CXCLs and their associated genes also promote tumor proliferation, inhibit apoptosis, and evade host immune responses through the AP-1 and NF-κB pathways remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…AP1 regulates gene expression in response to various stimuli such as cytokines, growth factors and stress signals. In ALK+ sALCLs AP1 fosters proliferation and survival via PI3K/Akt signaling and immune evasion by promoting program death-ligand 1 (PD-L1) transcription [ 56 ]. We have previously shown that PD-L1 expression, observed in more than 50% of BI-ALCL cases, was associated with copy number alterations at chromosome 9p24.1 in only 33% of the cases, suggesting the involvement of additional mechanisms in its upregulation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, AP-1 is another important transcription factor which is mainly involved in cell survival and proliferation [ 71 , 72 ]. Interestingly, PN has been shown to inhibit AP-1 DNA binding and transcriptional activity induced by UVB in a skin cancer model, thus exerting a chemopreventive activity [ 73 ].…”
Section: The Effect Of Parthenolide On Gene Expression Profilementioning
confidence: 99%